Live cell imaging of dynamic behaviors of motile cilia and primary cilium. (31st January 2019) - Ijaz, Faryal; Ikegami, Koji
Abstract : The cilium is a tiny organelle that projects from the surface of many cells and functions to generate fluid flow and/or sense extracellular signals from the environment. In this review, we present approaches for the successful imaging of dynamic behaviors of motile cilia and a primary cilium. Abstract: The cilium is a tiny organelle, with a length of 1–10 μm and a diameter of ~200 nm, that projects from the surface of many cells and functions to generate fluid flow and/or sense extracellular signals from the environment. Abnormalities in cilia may cause a broad spectrum of disease, i.e. the so-called ciliopathies. Multiple imaging approaches have been implemented to understand the structure, motion and function of the tiny cilium. In this review, we focus on the microscopic observations and analyses of the dynamic behaviors of both motile cilia and primary cilium. Motile cilia repeat reciprocal motions at 15–25 Hz with a clear asymmetry of effective and recovery strokes. Observing the fast movement of motile cilia requires a high-speed camera with a frame rate of more than 100 fps. The labeling of cilia tips enables the detailed analysis of the asymmetric beating motion of motile cilia. The primary cilium, which is imagined to be 'static, ' is also dynamic, i.e. it elongates, shrinks and disassembles, although this behavior is quite slower than that of motile cilia. The specific fluorescent labeling of primary cilium and time-lapse imaging are required to observe and analyze the slow behaviors of the primary cilium. We present some approaches, including some tips for successful procedures, in the successful imaging of the dynamic behaviors of motile cilia and primary cilium.